Flavanols and Flavanes from Crinum asiaticum and Their Effects on LPS Signaling Pathway Through the Inhibition of NF-κB Activation - Do, Kiep Minh; Shin, Min-Kyoung; Kodama, Takeshi; Win, Nwet Nwet; Prema, Prema; Nguyen, Hien Minh; Hayakawa, Yoshihiro; Morita, Hiroyuki (Planta Medica, 2021)
Three new flavanols, (2R,3S)-7-methoxy-flavan-3-ol (1), (2R,3S)-7-hydroxy-flavan-3-ol (2), and (2R,3S)-2′-hydroxy-7-methoxy-flavan-3-ol (3), together with two known flavans (4 and 5), were isolated from the chloroform extract of Crinum asiaticum. Their structures were elucidated by various spectroscopic methods, including 1D and 2D NMR, HR-ESI-MS, and CD data. The isolated compounds 1 and 3−5 showed inhibitory activity toward LPS-induced nitric oxide (NO) production. Further investigation of the NF-κB pathway mechanisms indicated that 1 and 3−5 inhibited the LPS-induced IL-6 production and p65 subunit phosphorylation of NF-κB in RAW264.7 cells, with an effective dose of 10 µM.
Keywords: Crinum asiaticum; flavans; flavanols; NO inhibition; NF-κB pathway